Strategies for Managing Low-probability, High-impact Events - Hiroki, Kenzo (World Bank, Washington, DC, 2013)
Every country should develop strategies for managing low-probability, high-impact extreme events-strategies that reflect their own as well as global experiences with mega-disasters. These strategies should integrate structural and nonstructural measures tailored to local conditions. Forecasting and early warnings, land-use planning and regulation, hazard maps, education, and evacuation drills are all vital. Lessons from the Great East Japan Earthquake (GEJE) can help improve these nonstructural practices, which in Japan have been shaped by trial and error after experiences with many natural disasters. The international community should develop knowledge-sharing mechanisms to help countries prepare for low-probability, high-impact extreme events.